Results of Onlay Preputial Flap Urethroplasty for the Single-Stage Repair of Mid- and Proximal Hypospadias - González, Ricardo; Lingnau, Anja; Ludwikowski, Barbara Magda (Frontiers in Pediatrics, 2018)
Aims To report current results of preputial flap onlay urethroplasty using the principle of the total preputial flap (TPF) for the one-stage repair of mid- and proximal hypospadias. Methods This study was a retrospective chart review of patients in a prospectively kept database of all hypospadias operations performed at two institutions from January 1 2011 to August 2017. Inclusion criteria: all patients who underwent hypospadias repair using a preputial only flap urethroplasty based on the principle of the TPF. Demographic data, duration of follow-up, complications, and reoperations were recorded. A successful result was considered to be a straight penis, a glanular meatus, and absence of voiding symptoms. Whenever possible an uroflow was obtained during the follow-up visits. Results Forty-nine children met the inclusion criteria. All patients had marked penile curvature. Three patients had chromosomal abnormalities. The mean age at the time of surgery was 22 months (11–110) and the mean duration of follow-up 23.4 months (1–79). In 48 cases, the urethral plate could be preserved without dividing it. The penile curvature was corrected with chordectomy alone in 10 patients, 38 required a dorsal plication of the tunica albuginea, and 1 required an additional ventral dermal graft. In 38 patients (77.5%), the initial operation was successful, and no further operations were needed. There were eight urethrocutaneous fistulas, three dehiscences of the glans approximation. One patient suffered a wound infection and partial loss of the flap. Conclusion One-stage repair of mid- and proximal hypospadias preserving the urethral plate and using a TPF for the urethroplasty and coverage of the ventral penis is successful in 77.5% of cases. Complications in the remaining patients were easily managed or did not require treatment. Compared to a planned two-stage approach, the technique described in this report resulted in significantly fewer procedures till complete resolution of the problem.